Attracting and retaining creative tourism entrepreneurs - Dias, Á.; González-Rodríguez, M. R.; Pereira, L.; Costa, R. (Creative Industries Journal, 2025)
Creative tourism entrepreneurs play an essential role in the competitiveness and innovation of a tourist destination. Moreover, they are more likely to find sustainable practices in their small-scale business than in large companies. However, despite this importance, the study of these entrepreneurs needs more attention, in particular knowledge about the factors that attract and retain them in a given destination. Thus, this research aims to identify the factors that are most valued by creative tourism entrepreneurs in relation to the characteristics of the destination. Based on a sample of 115 creative tourism entrepreneurs, we ran a two-step cluster analysis. The results showed that the most important factors were entrepreneurial culture, access to the market (tourists, visitors, etc.), creative atmosphere, quality of life and level of cooperation. The results also allowed us to identify two different segments of entrepreneurs: balanced and prospectors, which show different attitudes regarding the attraction factors and the willingness to stay in the destination. In the conclusion, the practical implications for destination management are discussed.